Leveraging Machine Learning for Insights and Predictions in Synthetic E-commerce Data in the USA: A Comprehensive Analysis - Islam, Md Rafiqul; Hossain, Miraz; Alam, Mahfuz; Khan, Medhat Mohiuddin; Rabbi, Md Masud Karim; Rabby, Md Fazlay; Bishnu, Kanchon Kumar; Das, Biswajit Chandra; Tarafder, Md Tanvir Rahman (Journal of Ecohumanism, 2025)
The primary purpose of this research was to leverage the potential of machine learning to extract meaningful information out of synthetic e-commerce data to overcome the limitations of traditional analysis. This research focused on the consumption patterns and trends of the US e-commerce market with specific knowledge of its idiosyncrasies and challenges. The synthetic e-commerce dataset comprises a comprehensive collection of simulated transactional data designed to reflect the dynamics of an online retail environment. The dataset included detailed records of customer transactions, capturing essential information such as transaction IDs, timestamps, product categories, quantities purchased, and total transaction values. Additionally, customer demographics are represented, encompassing attributes such as age, gender, location, and income levels, which facilitate deeper insights into consumer behavior and preferences. The dataset also featured product categories that range from electronics to apparel, allowing for diverse analyses of purchasing trends across different market segments. For model choice, we applied various machine learning algorithms specific to our needs of predicting sales, customer segmentation, demand forecast, and fraud detection. Random Forest, Logistic Regression, and K-Neighbors Classifier are the models selected by the analyst. For evaluating the performance of the models, we used a suite of metrics specific to the task at hand. For the case of fraud detection, the metrics included were accuracy, precision, recall, F1-score, and ROC-AUC. The heights of the bars indicated the accuracies of the models, with Random Forest being the highest, followed by KNN, and Logistic Regression being the least among the two models. The varying heights of the bars pictorially display the comparative performance of the models, with Random Forest being well ahead of the other two models. Machine learning-driven insights have transformed e-commerce business strategies by enabling data-driven strategies to improve pricing, marketing, and stock management. Using algorithms that consider historical sales patterns, rival pricing, and market conditions, companies can implement dynamic pricing strategies that change according to real-time conditions to maximize profit margins while being cost-effective. Integrating machine learning models with real-time anti-fraud systems is a key innovation in anti-fraud measures and risk management. Using complex algorithms that examine the data of transactions in real-time enables companies to detect potentially fraudulent activity while the activity is taking place.